Bid-to-cover and yield changes around public debt auctions in the euro area - Roel Beetsma; Massimo Giuliodori; Jesper Hanson; Frank de Jong (European Central Bank (ECB), 2017)
Earlier research has shown that euro-area primary public debt markets affect secondary markets. We find that more successful auctions of euro area public debt, as captured by higher bid-to-cover ratios, lead to lower secondary-market yields following the auctions. This effect is stronger when market volatility is higher. We rationalize both findings using a simple theoretical model of primary dealer behavior, in which the primary dealers receive a signal about the value of the asset auctioned.
Keywords: G11; G12; G14; G18; 330; public debt auctions; bid-to-cover ratios; primary and secondary markets; primary dealers; volatility